1997
DOI: 10.1016/s0022-5223(97)70175-2
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo lung model of pig-to-human hyperacute xenograft rejection

Abstract: This pig-to-human xenograft model suggests that the pig lung perfused with human blood has an early and violent hyperacute rejection that results in irreversible pulmonary dysfunction and failure within approximately 150 minutes of reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 26 publications
1
32
1
Order By: Relevance
“…Subsequent deposition of IgM, IgG, C1q, C3, C4, C9 will lead to the rapid failure of xenograft [3,18]. However, whether xenoreactive antibodies actually remain bound to swine endothelium is not certain [19].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent deposition of IgM, IgG, C1q, C3, C4, C9 will lead to the rapid failure of xenograft [3,18]. However, whether xenoreactive antibodies actually remain bound to swine endothelium is not certain [19].…”
Section: Discussionmentioning
confidence: 99%
“…11,[15][16][17] The mechanisms of hemolysis in organ xenoperfusion have not yet been fully elucidated. Two factors may be implicated in hemolysis during cross-circulation with xenogeneic ECLP.…”
Section: Discussionmentioning
confidence: 99%
“…27 It is reported that loss of anticoagulant functions of the endothelium leads to platelet aggregation and subsequent fibrin formation, which may then lead to erythrocyte fragmentation or microhemolysis. 25,28 Macchiarini et al 15 reported severe hemolysis in relation to intravascular thrombi of fibrin and platelet in extracorporeal pig lung perfusion with human blood. Moreover, RBC fragmentation promotes thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…121). In an attempt to overcome this incompatibility problem, transgenic pigs have been engineered that express human complement-regulatory proteins such as decay-accelerating factor (DAF) and CD59.…”
Section: Risks and Incompatibilities Associated With Using Pig Organsmentioning
confidence: 99%